The impact of the mountain climate on the oxygen supply system in human at different altitude - Radziejowski, P.; Rdziejowska, M.; Zukow, W. (Journal of Physical Education and Sport, 2019)
At the present time the mountainous climate as the ecosystem has been widely used in curative and sport practice with therapeutic, prophylactic and recreational purposes. This work aimed to study reactions of external breathing, blood circulation, blood and tissue respiration during ascending to mountain at various altitudes from 2100 m, 3500 m and 4200 m above sea level. To attain this goal, investigations were carried out to study changes in the functional respiratory system (FRS) and body`s oxygen regimes (BOR) in the people who have been well adapted to hypoxia of varying origin - sportsmen (adapted to physical loads of varying intensity) and altitude climbers (sportsmen, whose professional activity takes place under low and at time very low partial oxygen pressure in the inhaled air). Twenty-eight sport women and high altitude female climbers underwent complex examinations under normoxy conditions prior to ascending mountains. Later analogous examinations were conducted at the beginning (on day 2-3) of the educational-training session at mid-altitude (Terskol, PreElbrus, 2100 m above sea level) on day 10 of their stay. Examinations were conducted at altitudes 3500 and 4200 above sea level. Transfer of essentially healthy people, who have not been adapted to hypoxic hypoxia typical for mountains at altitude 2100 m above sea level, caused health worsening of FRS and BOR control. At altitude 4200 m above sea level even after 12 day acclimatization the indicators of external respiration were 2-2.5 times higher compared to same normoxy condition. After transfer to altitude 2100 m above sea level during first days of acclimatization it is desirable to reduce motor activity because under these conditions the state of the main oxygen-transport systems of the organism does not allow sustain work ability at normoxic level. It is desirable that such corrections be made individually with a consideration of data of prior stay at analogous altitude.